Art 2025 The Influence of Regional Potential Factors and Socio-Economic Barriers on People's Decisions to Use Sharia Insurance in Batu Bara Regency - Rima Mutia; Nur Ahmadi Bi Rahmani; Andri Soemitra (IAI Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2026)
This study aims to analyze the influence of regional potential and socio-economic barriers on people's decisions to use Islamic insurance in Batu Bara Regency. The study employs a quantitative approach using a survey method through questionnaires distributed to 97 respondents, determined using the Lemeshow formula with a 95% confidence level. The data were analyzed using multiple linear regression after passing classical assumption tests.The results show that partially, regional potential does not have a significant effect on people's decisions. Although the region has economic potential in the agriculture, fisheries, and MSME sectors, this has not been sufficient to encourage people to use Islamic insurance. On the other hand, socio-economic barriers have a positive and significant effect. Limited income, low literacy in Islamic finance, and the habit of relying on personal savings are the main factors influencing decisions.Simultaneously, both variables have a significant effect, with a coefficient of determination (R²) of 0.084, meaning that 8.4% of the variation in people's decisions can be explained by the research model. This study concludes that the development of Islamic insurance should focus on improving literacy, providing easily understandable education, and expanding service access so that public interest can be translated into actual decisions.